Dasar-Dasar Kewirausahaan Meningkatkan Pemasaran Digital Dengan Pemanfaatan Media Sosial - Fira, Sri Asfirawati Halik; Faizah, Andi Nurul; Perawati; Farida (LPPM Universitas HKBP Nommensen, 2024)
Community service is an implementation of practicing science to the community with institutions as a form of implementation of the Tri Dharma of Higher Education. For an entrepreneur in the development of his business, social media is very necessary in marketing, especially in the current digitalization era. This service activity was carried out in Bonto Bangun Village, especially for UMKM business actors. Hopefully with this activity we hope to contribute knowledge to entrepreneurs in supporting the marketing of their products digitally through packaging design, use of social media and promotion of their businesses so that after this dedication can increase the public's buying interest in the business of UMKM actors in Bonto Bangun village.